LIFE QUALITY ASSESSMENT IN PHTHISIOPEDIATRICS - D. N. Adzhablaeva (Туберкулез и болезни лёгких)
Objective: to analyze the initial life quality in children and adolescents when using various methods of tuberculosis detectionSubjects and methods. Using the questionnaire of Pediatric Quality of Life Inventory (PedsQL) life quality was assessed in 90 adolescents in the age from 13 to 17 years oldResults. The impact of a chronic disease on the life quality of children and adolescents had some relevance to gender: boys' sufferings were mostly physical while girls had rather emotional problems Adolescents at the age of 15-17 years old reported much low life quality compared to the children of 13-14 years old Groups of children detected by self-referral for medical care had lower life quality rates compared to the average ones in all examined children Such aspects as school and physical functioning were compromised the most in children and adolescents detected through diaskintest and digital fluorography While the children detected by self-referral reported their emotional and psycho-social well-being to be the worst one, and the latter had the abrupt reduction of those parameters in adolescents with disseminated and destructive forms of tuberculosis The wider and more invasive testing methods were, the more severe reduction of life quality was observed Thus the priority is to be given to diagnostics with diaskintest versus diagnostics by self referral